PENGARUH PEMBERIAN GLUTATHIONE PRA LATIHAN SUBMAKSIMAL TERHADAP JUMLAH TROMBOSIT DAN MASA PERDARAHAN : STUDI EKSPERIMENTAL PADA HEWAN COBA - Hesty Rohmatul Fajri; Raden Argarini; Choesnan Effendi (Sport and Fitness Journal, 2015)
Submaximal activity leads to oxidative stress that causes cellular damage, including platelet. Glutathione as a potential antioxidant has cellular protective effect. The purpose of this research was to analize the effect of glutathione pre submaximal exercise on platelet count and bleeding time. The study used separate post test only control group design with 28 male rats (Rattus norvegicus, Wistar strain) which were divided into four groups : P1(6) without intervention; P2(7), P3(8), and P4(7) with administration of placebo (aquabidest), glutathione 54 mg/kgBB, and glutathione 108 mg/kgBB intraperitoneally for each group that were given 5 times, continued with submaximal exercise (swimming with 4% of weight load). The result of ANOVA and LSD test showed that submaximal exercise had tendency to decrease platelet count (p=0,407; not significant) and prolonged bleeding time (p=0,017). Glutathione pre submaximal exercise had tendency to increase platelet count (p=0,407; not significant) and shortened bleeding time (p=0,017). Glutathione with a dose of 54 mg/kg had protective effect on platelet better than a dose of 108 mg/kg. In conclusion, the administration of glutathione pre submaximal exercise has protective effect on platelet in male rats (Rattus norvegicus).